2006
DOI: 10.1007/s10661-006-9397-0
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical and Experimental Study of Pollutant Dispersion in a Traffic Tunnel

Abstract: Three-dimensional turbulent flow and dispersion of gaseous pollutants carbon monoxide (CO) and nitrogen oxides (NOx) in a road tunnel was modeled using the standard k-epsilon turbulence model and solved numerically using the finite volume method. Vehicle emissions were estimated from the measured traffic flow rates and modeled as banded line sources along the tunnel floor. The effects of fan ventilation and piston effect of moving vehicles on the airflow and pollutant dilution were examined. The numerical resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The research on the comparison of flow performance in a pipe with three different RANS models, namely k-e, k-x, Reynolds stress models (RSM), is found that the simulation results among the three models in the mean velocity profile and the friction factor match quite well with the experimental results and RSM consumes more time though it can give some additional information on the shear stress correlations (Vijiapurapu and Cui, 2010). Furthermore, the standard k-e turbulent model has the advantage of being extensively used in simulation of tunnel ventilation and has been validated against the experimental data (Chung and Chung, 2007;Vega et al, 2008;Solazzo et al, 2008;Huang et al, 2008). Accordingly, the standard k-e turbulent model due to Launder and Spalding (Launder and Spalding, 1974) was adopted in this research.…”
Section: Governing Equationsmentioning
confidence: 73%
See 4 more Smart Citations
“…The research on the comparison of flow performance in a pipe with three different RANS models, namely k-e, k-x, Reynolds stress models (RSM), is found that the simulation results among the three models in the mean velocity profile and the friction factor match quite well with the experimental results and RSM consumes more time though it can give some additional information on the shear stress correlations (Vijiapurapu and Cui, 2010). Furthermore, the standard k-e turbulent model has the advantage of being extensively used in simulation of tunnel ventilation and has been validated against the experimental data (Chung and Chung, 2007;Vega et al, 2008;Solazzo et al, 2008;Huang et al, 2008). Accordingly, the standard k-e turbulent model due to Launder and Spalding (Launder and Spalding, 1974) was adopted in this research.…”
Section: Governing Equationsmentioning
confidence: 73%
“…The outflow boundary condition is used at the tunnel outlet, namely @U=@n ¼ 0 (where U = u, k or e). The fans inlet also adopts the outflow boundary condition (Chung and Chung, 2007). The jet fans velocity U j = 33 m/s is specified for the fan outlet according to the actual design data.…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 3 more Smart Citations